An interesting case of a twin pregnancy complicated with happy hypoxia, peripartum cardiomyopathy and haemolysis, elevated liver enzymes, low platelet count syndrome during the COVID-19 pandemic situation - Banerjee, Ramna; Rahman, Farheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ever since the beginning of the COVID-19 pandemic in December 2019, the focus has been on studying the varying clinical symptoms and signs of the disease. A condition which has been alarmingly occurring in quite a number of patients is a state of hypoxemia, of which the patient is blissfully unaware and does not have any symptoms of breathlessness or respiratory discomfort in spite of having low oxygen saturation levels. Hence the term coined for it- “happy hypoxemia”. We are reporting a case of a pregnant woman with twin pregnancy and pregnancy induced hypertension who rapidly progressed to hemolysis, elevated liver enzymes, low platelets syndrome without having proteinuria along with features of peripartum cardiomyopathy and also had low oxygen saturation levels (less than 72%) though she did not have any complaints of dyspnea, orthopnea, hemoptysis, chest pain, cough or peripheral oedema. She was tested for COVID-19 with real-time polymerase chain reaction on 2 occasions a week apart and was found to be negative. Her recovery was also unexpectedly rapid and progressive.